1980
DOI: 10.1073/pnas.77.7.3903
|View full text |Cite
|
Sign up to set email alerts
|

Posttranscriptional regulation of an erythromycin resistance protein specified by plasmic pE194.

Abstract: Induction of the synthesis of a plasmid-encoded polypeptide (E3) by erythromycin is known to be required for the inducible expression of resistance to the macrolide-lincosamide-streptogramin B group of antibiotics in Bacillus subtilis strains carrying the plasmid pE194. This resistance is mediated by a specific N6-dimethylation of adenine in the 23S rRNA of the large ribosomal subunit. We show in this report that E3 induction is regulated posttranscriptionally in the sense that it can occur when RNA synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

1981
1981
1993
1993

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 29 publications
(28 reference statements)
5
58
0
Order By: Relevance
“…hour, when it remained constant. Others have invoked feedback inhibition or an autoregulation mechanism to account for the constant level of ermC product in bacterial cells (Shivakumar et al, 1980;Gryczan et al, 1978). The optimal culture time for methylase activity, following Em induction of ermJ was concluded to be The molecular mass of the purified rRNA methyltransferase was determined by gel permeation chromatography using Sephadex G-100.…”
Section: Characterization Of Rrna Methyltransferusementioning
confidence: 99%
See 1 more Smart Citation
“…hour, when it remained constant. Others have invoked feedback inhibition or an autoregulation mechanism to account for the constant level of ermC product in bacterial cells (Shivakumar et al, 1980;Gryczan et al, 1978). The optimal culture time for methylase activity, following Em induction of ermJ was concluded to be The molecular mass of the purified rRNA methyltransferase was determined by gel permeation chromatography using Sephadex G-100.…”
Section: Characterization Of Rrna Methyltransferusementioning
confidence: 99%
“…(Weisblum,19SS), translational feedback inhibition (Shivakumar et al, 1980) or autoregulation (Breidt & Dubnau, 1990). Translational attenuation is the most important mechanism and has been studied intensively.…”
Section: Introductionmentioning
confidence: 99%
“…The ermC gene, together with sequences responsible for inducibility has been localized on the physical map of pE194, the direction of transcription has been determined, and the ermC gene and flanking DNA regions have been sequenced (12,13,14). Recently we have reported that the induction of the 29K ermC product is regulated posttranscriptionally and that interaction of Em with a binding site on a sensitive (undermethylated) ribosome is required for induction (15). Based on these findings, a model for ermC regulation has been proposed (13,14,16).…”
Section: Introductionmentioning
confidence: 99%
“…Three plasmid-encoded elements are used in RCR: a plus origin, a replication protein (Rep) and a minus origin Plasmid pE194 encodes the ermC gene, which confers inducible MLS resistance, and it is to date the only member of its family. pE194 is 3.7 kb in size, and has been extensively studied in both S. aureus (Weisblum et al, 1979;Iordanescu & Surdeanu, 1980;Byeon & Weisblum, 1990;Sozhamannan et al, 1990) and Bacillus subtilis (Gryczan et al, 1980;Shivakumar et al, 1980;Horinouchi & Weisblum, 1982).…”
Section: Introductionmentioning
confidence: 99%